(untitled) (Journal of Educational Sciences, 2019)
The article presents the analysis system of the “house” archetype in N. Verevochkin’s novel “The Mammoth’s Tooth”, which is based on the key principles of psychological and pedagogical science: the- ories of S.L. Rubinstein on the nature of thinking, N.A. Menchinskaya on the formation of the worldview as an integrative feature of the personality of students, Yu.A. Samarin on the relationship of associations and semantic connections, on the achievement of a system-activity, personality-oriented approach in education. The methodical system for analyzing “the house” archetype in N. Verevochkin’s novel “The Mam- moth’s Tooth” is based on the use of various effective methods of interactive, heuristic training and means of forming critical thinking, in the amount of which contribute to the development of students as full subjects of the cognitive process, which is necessary for their successful professional activity as teachers of Russian language and literature. The author of the article proposes to orient students to take into account the originality of the post- modern poetics of Verevochkin’s novel “The Mammoth’s Tooth”. Students linked the archetype of the house with the creative method of the writer. Work on the novel “The Mammoth’s Tooth”contributes to the formation of a new look at students of modern Russian literature of Kazakhstan. The traditional method of studying the works of Russian literature of our republic relies on the analysis of the content of the works, and, unfortunately, not enough attention is paid to the artistic form. The system of analysis of the archetype of the house in Verevochkin’s novel “The Mammoth’s Tooth”, proposed and tested in this study, can be the basis for a comprehensive study of all modern Rus- sian prose of Kazakh literature in the light of the stated topic. Key words: N. Verevochkin, novel “The Mammoth’s Tooth”, archetype “house”, postmodernism, methodical analysis, methodical system, heuristic method.